Phonon optics, thermal expansion tensor, thermodynamic and chemical bonding properties of Al4SiC4 and Al4Si2C5: a first-principles study. Issue 49 (3rd May 2016) - Li, Y. F.; Xiao, B.; Sun, L.; Gao, Y. M.; Cheng, Y. H.
Abstract : The creation of stacking fault in Al4 SiC4 crystal structure due to a phonon mode (E1, 139.7 cm −1, Raman active) at Γ -point with negative mode-Grüneisen constant (−0.28). (a) 3-D side-view; (b) 2-D side view. Abstract : The phonon spectra, chemical bonding, thermal and thermodynamic properties of Al4 SiC4 and Al4 Si2 C5 are calculated by first-principles using density functional theory. Raman and infrared (IR) active phonon modes and their eigenvectors are analyzed. Phonon mode-Grünseisen parameter and macroscopic Grünseisen constants are evaluated from phonon spectra. Employing quasiharmonic approximation (QHA), the thermal expansion tensor is obtained. The calculated volumetric thermal expansion coefficient (TEC) of Al4 SiC4 is high than that of Al4 Si2 C5 ; and the linear TEC in the [001] direction is slightly higher than that of the [100] direction for both compounds. The computed average linear TECs for Al4 SiC4 and Al4 Si2 C5 are 9.96 × 10 −6 K −1 and 8.9 × 10 −6 K −1 in a range from room temperature to 1500 K, respectively. Other thermal properties such as specific heats ( C V, and C P ), entropy ( S ), isothermal and isobaric bulk moduli ( K T and K S ) are also discussed. Using Slack's model, it is found that thermal conductivities are 59.9 W m −1 K −1 and 78.3 W m −1 K −1 at room temperature for Al4 SiC4 and Al4 Si2 C5, respectively. The response of chemical bonds to hydrostatic pressure is discussed using Milliken population analysis. We also plot the charge density and its reduced density gradient to reveal the covalent bonds in the structure.